Examining for Cavum Septum Pellucidum and Ventricular Enlargement in Retired Elite-Level Rugby League Players - Stanwell, Peter; Iverson, Grant L.; Van Patten, Ryan; Castellani, Rudolph J.; McCrory, Paul; Gardner, Andrew J. (Frontiers in Neurology, 2022)
Objective: A cavum septum pellucidum (CSP) has been reported as a visible brain anomaly in normal individuals as well in some former combat and collision sport athletes. The appearance of CSP with fenestrations and ventricular enlargement are considered associated features of the neuropathological diagnosis of chronic traumatic encephalopathy. The current study examined CSP anatomic features and lateral ventricle size in retired elite rugby league players and controls. Methods: Forty-one retired rugby league players and 41 healthy community controls, similar in age and education, underwent structural MRI scans. CSP grade, CSP length, corpus callosum septal length, and Evans’ ratio (for lateral ventricle size) were rated by two of the current study authors. All participants also self-reported concussion exposure histories, depressive symptoms, daytime sleepiness, and impulsivity. They completed a neuropsychological test battery assessing premorbid intellectual functioning, attention, processing speed, language, visuospatial skills, memory, and aspects of executive functioning. Results: The two raters had high agreement for CSP grade (Cohen’s κ=.80), CSP length (intraclass correlation [ICC]=.99), corpus callosum septal length (ICC=.73), the CSP/septal ratio (ICC=.99), and the Evans’ ratio (ICC=.75). Twenty-five retired players (61.0%) had an abnormal CSP compared to 17 controls (41.5%; χ2(1, 82)=3.12, p=.08, odds ratio=2.21). The CSP/septal ratio was larger for retired players than for the controls. The Evans’ ratio did not differ between the two groups. In the retired rugby league players (n=41), those with normal (n=16) and abnormal (n=25) CSP grades did not differ across age, age of first exposure to collision sport, years of sport exposure, concussion history, or 23 clinical and cognitive variables. Conclusion: This study revealed a difference in the size of the CSP between retired professional rugby league players and controls. There was no significant difference in the size of the ventricles between the two groups. There were no significant differences between those with versus without an abnormal CSP on age of first exposure to rugby league, years of exposure to repetitive neurotrauma, number of lifetime concussions, depression, impulsivity, perceived cognitive decline, or on any neuropsychological test.